(untitled) (Bangladesh Pharmaceutical Journal, 2016)
Periodontitis is a local infection in the gingival crevices, which affects the structural organs surrounding the teeth like periodontal ligament, connective tissue and bone. Ornidazole is an antimicrobial drug widely used to treat periodontitis. The primary objective of this study was to design and evaluate periodontal films of ornidazole for placement into the periodontal pockets for targeted delivery of drug. Nine formulations (F1 to F9) were prepared by solvent casting method using polymer A, polymer B and plasticizer A. Chloroform and dichloromethane were used as solvent system. The API and dental films were then evaluated for various parameters including trinocular microscopic image, melting point, weight variation, thickness, folding endurance, surface pH, swelling index, percentage moisture loss, antimicrobial activity, content uniformity, in vitro drug release and release kinetics as well as RTIR and DSC. Formulation F1 showed the minimum weight and thickness and F9 showed the maximum. It was observed that weight and thickness of film were directly proportional to the total solid content of the film. RSDs of content uniformity test for all the batches were below 3.0%. Folding endurance and swelling index of films were inversely proportional to the amount of polymer in the film. The surface pH of all the batches were between 6-7. Formulation F1 revealed the maximum percentage of moisture loss (19.34%), while F8 showed the minimum (3.654%). Formulation F2 demonstrated data the highest zone of inhibition (21.91 mm). Bangladesh Pharmaceutical Journal 19(2): 133-146, 2016